2012
DOI: 10.1186/1471-2458-12-233
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder features in indigenous Aboriginal and Torres Strait Islander Australian Peoples

Abstract: BackgroundObesity and related cardiovascular and metabolic conditions are well recognized problems for Australian Aboriginal and Torres Strait Islander peoples. However, there is a dearth of research on relevant eating disorders (EDs) such as binge eating disorder in these groups.MethodsData were obtained from interviews of 3047 (in 2005) and 3034 (in 2008) adults who were participants in a randomly selected South Australian household survey of individuals' age > 15 years. The interviewed comprised a general h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
(16 reference statements)
2
17
0
3
Order By: Relevance
“…Our findings indicate that indigenous Australians are certainly not immune from disordered eating, with rates of each feature assessed being equivalent to those of the non-indigenous sample. The results of this study mirror those of the only other study assessing the prevalence of ED features in indigenous Australians [ 26 ], which also found rates of ED features to be comparable between indigenous and non-indigenous participants. Furthermore, these findings are consistent with studies of indigenous peoples from other nations.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings indicate that indigenous Australians are certainly not immune from disordered eating, with rates of each feature assessed being equivalent to those of the non-indigenous sample. The results of this study mirror those of the only other study assessing the prevalence of ED features in indigenous Australians [ 26 ], which also found rates of ED features to be comparable between indigenous and non-indigenous participants. Furthermore, these findings are consistent with studies of indigenous peoples from other nations.…”
Section: Discussionsupporting
confidence: 83%
“…A study comparing cognitive behavioural therapy (CBT) in BN delivered in person versus via telemedicine found that CBT via telemedicine had comparable outcomes to face-to-face CBT and was readily accepted by patients [ 40 ]. Finally, as this study and other research [ 26 , 37 ] have shown disordered eating behaviours to occur at similar rates amongst indigenous and non-indigenous persons, it is vital that culturally sensitive ED services with staff who have been trained and are experienced in the treatment of indigenous persons are made available, especially considering the high burden of obesity and weight-related health problems in this population.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, epidemiologic evidence indicates that Aboriginal and Torres Strait Islander people are no less likely, and may be more likely, to experience an eating disorder as non-indigenous Australians (Hay and Carriage, 2012). However, epidemiologic evidence indicates that Aboriginal and Torres Strait Islander people are no less likely, and may be more likely, to experience an eating disorder as non-indigenous Australians (Hay and Carriage, 2012).…”
Section: General Principles Of Treatment For All Eating Disordersmentioning
confidence: 99%
“…The authors suggested that compared to the non-Indigenous population, a relatively higher proportion of First Australians reported binge eating, subjective binge eating and purging behaviours. These data were limited by the sample size (total n = 3047, First-Australians n = 85) and that eating disorders to the diagnostic threshold level were not assessed [5]. A systematic synthesis of population health data in adolescent First Australians suggested eating disorders were more likely to affect non-Indigenous Australians compared to First Australians, and were more likely to affect First Australians in urban areas compared to remote areas, as no eating disorder cases were identified in remote areas [6].…”
Section: Prevalence Of Eating Disorders Amongst First Australiansmentioning
confidence: 99%